Trinidad /The Fish Market. - (:unkn) unknown (My University, 2010)
Several fishing boats rest on the calm water of a sheltered port area, as men and women walk along a roadway set between the sea and a set of buildings. Coconut trees and other foliage draw the eyes across to the mountains seen in the distance. Affixed to the postcard which is dated January 14, 1936 is a Trinidad and Tobago three cents stamp. The addressee is Dorothy ---? from The Traphagen School of Fashion, New York City, USA.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Harbors; Boats and boating; Fishing ports; Markets; 1936